2015
DOI: 10.1073/pnas.1517124112
|View full text |Cite
|
Sign up to set email alerts
|

FOXO regulates RNA interference in Drosophila and protects from RNA virus infection

Abstract: Small RNA pathways are important players in posttranscriptional regulation of gene expression. These pathways play important roles in all aspects of cellular physiology from development to fertility to innate immunity. However, almost nothing is known about the regulation of the central genes in these pathways. The forkhead box O (FOXO) family of transcription factors is a conserved family of DNAbinding proteins that responds to a diverse set of cellular signals. FOXOs are crucial regulators of cellular homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 46 publications
3
75
0
Order By: Relevance
“…Their identification using the currently developed screen protocol is underway. In this regard, it is noteworthy that a basic leucine zipper-type and a forkhead box O-type transcription factor have been shown to regulate RNA silencing genes in plant and insect, respectively (29,46). It will also be of interest to further explore whether SAGA, conserved across eukaryotic organisms from yeast to humans, serves as an RNAi regulator in these organisms and what viral factors determine the virus-specific RNAi activation and requirement of AGL2 for RNAi induction.…”
Section: Saga Mediates Virus-responsive Induction Of Rnai Key Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their identification using the currently developed screen protocol is underway. In this regard, it is noteworthy that a basic leucine zipper-type and a forkhead box O-type transcription factor have been shown to regulate RNA silencing genes in plant and insect, respectively (29,46). It will also be of interest to further explore whether SAGA, conserved across eukaryotic organisms from yeast to humans, serves as an RNAi regulator in these organisms and what viral factors determine the virus-specific RNAi activation and requirement of AGL2 for RNAi induction.…”
Section: Saga Mediates Virus-responsive Induction Of Rnai Key Genesmentioning
confidence: 99%
“…Mechanisms of its transcriptional regulation remain largely unknown but appear to be regulated differently in different organisms (5,6,29,30). We have developed a genetic screen protocol using an infectious cDNA clone of a CHV1 mutant, Δp69, which lacks a viral suppressor of RNA silencing (VSR), p29, and induces the key RNAi genes excessively (Fig.…”
Section: Saga Mediates Virus-responsive Induction Of Rnai Key Genesmentioning
confidence: 99%
“…FOXO activity is significantly higher in D. melanogaster larvae with genetically ablated corpora allata , the organ that produces JH (Mirth et al, 2014). Overexpression of dFOXO increases oxidative stress tolerance (Giannakou et al, 2004; Hwangbo et al, 2004) while dFOXO-null mutants are more sensitive to oxidative stress (Jünger et al, 2003) and deficient in viral defence (Spellberg and Marr, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The requirement for base-pairing prior to initiation of degradation provides great specificity and mechanisms for enhancement of efficiency have also evolved such as amplification via DNA forms and production of secondary siRNAs followed by systemic spread via exosomes [74,75]. On the other hand, efficiency of antiviral RNAi can be affected by physiological conditions such as nutritional status and stress [19,168]. Furthermore, during persistent viral infections, the RNAi pathway may be partially dismantled or may function in different ways that are not completely understood [206].…”
Section: Resultsmentioning
confidence: 99%
“…When energy levels are low and insulin/insulin-like growth factor signaling is reduced, the forkhead transcription factor dFOXO responds by translocation to the nucleus resulting in increased target gene expression [18]. It was observed that induction of dFOXO in transgenic flies results in increased expression of the RNAi machinery genes ago-1, ago-2 and dcr-2 and concomitant resistance to virus infection [19]. In dFOXO null flies, the greater susceptibility to RNA viruses can be rescued by over-expression of Dcr-2.…”
Section: Introductionmentioning
confidence: 99%